2010
DOI: 10.1186/1757-7241-18-64
|View full text |Cite
|
Sign up to set email alerts
|

Systemic central venous oxygen saturation is associated with clot strength during traumatic hemorrhagic shock: A preclinical observational model

Abstract: BackgroundClot strength by Thrombelastography (TEG) is associated with mortality during trauma and has been linked to severity of tissue hypoperfusion. However, the optimal method for monitoring this important relationship remains undefined. We hypothesize that oxygen transport measurements will be associated with clot strength during traumatic shock, and test this hypothesis using a swine model of controlled traumatic shock.MethodsN = 33 swine were subjected to femur fracture and hemorrhagic shock by controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Thromboelastography (TEG; TEG 5,000, Haemoscope, Niles, IL) by recalcification (10 mM final calcium concentration) was performed in whole blood at 37°C 30 min after blood draw as described previously (54). TEG parameters measured included clot onset time (R), clot formation (or kinetics) time (K), clotting angle (Angle), maximal clot strength (MA), and shear elastic modulus (G).…”
Section: Methodsmentioning
confidence: 99%
“…Thromboelastography (TEG; TEG 5,000, Haemoscope, Niles, IL) by recalcification (10 mM final calcium concentration) was performed in whole blood at 37°C 30 min after blood draw as described previously (54). TEG parameters measured included clot onset time (R), clot formation (or kinetics) time (K), clotting angle (Angle), maximal clot strength (MA), and shear elastic modulus (G).…”
Section: Methodsmentioning
confidence: 99%
“…Preclinical studies have primarily focused on evaluating the combined effects of trauma and hemorrhage on coagulation impairments, clotting status, and blood loss. 32 81 82 83 84 85 86 87 88 Hemorrhage severity greatly impacts the metabolic markers, 86 87 physiological and coagulation responses observed in animal models, with varying percentages used to mimic different degrees of blood loss seen in trauma patients. Studies have found that hemorrhage and tissue injury significantly reduced arterial blood pressure, cardiac index, hemoglobin, hematocrit, and platelet count.…”
Section: Resultsmentioning
confidence: 99%
“…Coagulation function was affected by apheresis, hemorrhage, and resuscitation with different solutions, with a reduction in fibrinogen levels resulting in a significant decrease in clot strength. 81 82 83 84 Therapy with high-dose fibrinogen concentrate and the transfusion of platelets were found to restore coagulation function. 85 Also, resuscitation with shed whole blood or FFP has demonstrated greater efficacy than PlasmaLyte in maintaining blood pressure and TEG maximum amplitude.…”
Section: Resultsmentioning
confidence: 99%
“…Massive haemorrhage has previously been studied in swine models [20-24], but only a few have studied the effect of hypoperfusion in combination with soft tissue injury and fractures in the initial phase prior to fluid resuscitation [25,26]. White et al studied the effect on conventional coagulation parameters as well as thrombelastography using TEG, in a model of injured and haemorrhaged swine.…”
Section: Discussionmentioning
confidence: 99%